From animal to plant sentience: Is there credible evidence? - Dung, Leonard (Animal Sentience, 2023)
Segundo-Ortin & Calvo argue that plants have a surprisingly varied and complex behavioral repertoire. Which of these behavioral capacities are credible indicators of sentience? If we use the standards of evidence common in discussions of animal sentience, the behavioral capacities reviewed are insufficient evidence of sentience. Even if some putative indicators of animal sentience are present in plants, it is not clear whether what we should conclude is that plants are sentient or that those indicators are inadequate.
CRIS-Team Scopus Importer:2023-05-26